2019
DOI: 10.1111/jopy.12531
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive integration of personal or public events affects mental health: Examining memory networks in a case of natural flooding disaster

Abstract: Objective The purpose of this research was to examine whether memories of personal or public events could affect mental health through the way those memories are integrated in memory networks. Method Participants from the general population (N = 224, age mean = 36.62 years, 74% female) were either directly or indirectly personally affected by a natural flooding disaster with moderate consequences or had simply learned about it. A prospective design (during the floods and two months later) was used to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Many have perceived their basic needs as thwarted as they lost control over their usual occupations, they were cut off from their loved ones, and authorities disseminated mixed messages because they did not (and still do not) fully understand the new virus. Such stressful events are likely to reactivate the recall of past personal life events that were need thwarting in a similar fashion (e.g., experiences of ostracism, natural disasters, or other traumas), thus exacerbating the current thus exacerbating the thwarted needs related to the pandemic experience ( Philippe and Houle, 2020 ). A vulnerability to the reactivation of such need thwarting memories can motivate one to retrieve significance by finding compensatory ways to fulfill those needs, making one cognitively receptive to new narratives.…”
Section: Conspiracy Theoriesmentioning
confidence: 99%
“…Many have perceived their basic needs as thwarted as they lost control over their usual occupations, they were cut off from their loved ones, and authorities disseminated mixed messages because they did not (and still do not) fully understand the new virus. Such stressful events are likely to reactivate the recall of past personal life events that were need thwarting in a similar fashion (e.g., experiences of ostracism, natural disasters, or other traumas), thus exacerbating the current thus exacerbating the thwarted needs related to the pandemic experience ( Philippe and Houle, 2020 ). A vulnerability to the reactivation of such need thwarting memories can motivate one to retrieve significance by finding compensatory ways to fulfill those needs, making one cognitively receptive to new narratives.…”
Section: Conspiracy Theoriesmentioning
confidence: 99%
“…Moreover, past research has also shown that people who present an integrative regulation style tend to accept and tolerate negative events or emotions without feeling overwhelmed, disorganized, or defensive. These skills are linked to psychological well‐being and growth over time (Houle & Philippe, 2020 ), even throughout stressful collective events, such as natural disasters (Philippe & Houle, 2020 ). Other potential protective factors, such as self‐care practices, should also be empirically examined (Barnett et al, 2007 ; Bloomquist et al, 2015 ; Bober et al, 2006 ; Posluns & Gall, 2020 ; Saakvitne & Pearlman, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 If a need-thwarting memory is part of an overall need-satisfying network, these need-satisfying networked memories should reduce the negative impact of the main need-thwarting memory. Conversely, a need-satisfying memory part of a network with other need-thwarting networked memories will result in an attenuation of the positive impact of the main need-satisfying memory (e.g., Philippe & Houle, 2020). Thus, in certain cases, the effect of the networked memories can surpass the one of the main memory (e.g., Philippe, Dobbin, Ross, & Houle, 2018;Philippe & Houle, 2020), although both typically contribute independently to outcomes (e.g., Demblon et al, 2016;Philippe et al, 2012).…”
Section: The Effects Of Adult Attachment Insecurity On Couple Adjusmentioning
confidence: 99%